Empowering Arabic Reading Skills through Interactive Digital Worksheets: A Development Study Using Liveworksheet - Zizah, Rifqi (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2025)
Despite technological advancements in education, Arabic reading instruction at the elementary level largely relies on conventional methods that hinder student engagement and learning outcomes. This study aimed to develop Arabic reading instructional materials utilizing the Liveworksheet platform to foster active and engaging learning experiences for elementary students. The research employed the ADDIE model, encompassing the stages of Analysis, Design, Development, Implementation, and Evaluation. Conducted at SD Islam Sabilillah Jombang, this study involved 25 fifth-grade students as research participants. The findings demonstrate that the developed materials effectively enhanced students’ reading skills, as indicated by the increase in the average pretest score from 54.04 to 78.08 in the posttest, with an N-Gain score of 0.65, categorized as moderate improvement. The interactive features of Liveworksheet, including drag and drop, multiple-choice, and short-answer activities, successfully promoted active student engagement. This study supports the integration of interactive digital media in Arabic language education and offers a practical solution to improve elementary students’ reading skills.